Interspeech 2019 2019
DOI: 10.21437/interspeech.2019-2528
|View full text |Cite
|
Sign up to set email alerts
|

The Processing of Prosodic Cues to Rhetorical Question Interpretation: Psycholinguistic and Neurolinguistics Evidence

Abstract: In many languages, rhetorical questions (RQs) are produced with different prosodic realizations than string-identical information-seeking questions (ISQs). RQs typically have longer constituent durations and breathier voice quality than ISQs and differ in nuclear accent type. This paper reports on an identification experiment (Experiment 1) and an EEG experiment (Experiment 2) on German wh-questions. In the identification experiment, we manipulated nuclear pitch accent type, voice quality and constituent durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…This result clearly goes in the same direction and has the same magnitude as [10]. Previous perception data have shown that listeners make use of prosodic cues to RQ vs. ISQ meaning [25,26] in an experimental setting. Here, we show that speakers use these cues also in spontaneous settings to help their listeners deduce the intended meaning.…”
Section: Discussionsupporting
confidence: 65%
“…This result clearly goes in the same direction and has the same magnitude as [10]. Previous perception data have shown that listeners make use of prosodic cues to RQ vs. ISQ meaning [25,26] in an experimental setting. Here, we show that speakers use these cues also in spontaneous settings to help their listeners deduce the intended meaning.…”
Section: Discussionsupporting
confidence: 65%
“…The set of stimuli consisted of 32 German wh-questions (e.g., Who likes lemon? ), which were manipulated by fully crossing four factors: (a) nuclear accent type (late-peak vs. early-peak accent), (b) voice quality (breathy vs. modal voice on the final noun of the wh-question), and (c) duration of the utterance (lengthening or shortening of the utterance duration by 10%), resulting 64 test trails in eight test conditions (cue combinations) (see [14]) in (d) two different experimental settings (Experiment I vs. Experiment II) summing up to 16 conditions in total.…”
Section: Methodsmentioning
confidence: 99%
“…We used the probabilities in Figure 1 for the 16 test conditions. The proportions in Experiment I were taken from the outcome of a psycholinguistic experiment [14,16,23] while the proportions of Experiment II were entirely hypothetical in nature:…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In rhetorical questions and exclamatives, the (LH)* accent is accompanied by further prosodic modification, in particular lengthening and non-modal voice quality Wochner, Forthcoming), not necessarily co-occurring with the accented word but occurring across the utterance. Listeners, in turn, do not only use information on the pitch accent type when identifying rhetorical questions, but additionally use durational and voice quality cues (Kharaman et al, 2019). Intensity and voice quality could not be analyzed with the present data set because of remote data collection; the fact that 13 The words are not even listed in the CELEX corpus (Baayen et al, 1993); dlexDB (Heister et al, 2011) reveals a very low frequency, ranging from 1 for "Mandalas" (0.43 occurrences per million) to 116 for "Melanie" (50.43 o.p.m.).…”
Section: Crosstalk Between Tone and Intonation And Cross-linguistic I...mentioning
confidence: 99%